Infrared-radiofluorescence: dose saturation and long-term signal stability of a K-feldspar sample - Kreutzer, Sebastian; Mercier, Norbert; Lamothe, Michel (Radiation measurements, 2022)
Infrared radiofluorescence (IR-RF) of K-feldspar is a luminescence dating method proposed for chronologies of older sediments in Quaternary science. Its key advantages are higher saturation doses than optically stimulated quartz luminescence and long-term stability (no fading). However, while successful dating applications using IR-RF seem to become more frequent, both key advantages, dose saturation and signal stability, are still insufficiently constrained. Here we report on IR-RF spectrometry and spatially resolved IR-RF measurements of batches of one K-feldspar sample from the Médoc area in Southwest France. The RF spectrometry measurements revealed a bright decaying RF peak at ca 1.43 eV (867 nm), and component deconvolution of 528 spectra revealed additional peaks at ca 1.37 eV (905 nm), ca 1.71 eV (725 nm), ca 2.2 eV (564 nm), and ca 2.7 eV (459 nm). Confirmed by spatially resolved IR-RF measurements, dose-response measurements reveal that a given additive gamma-dose can be reproduced up to 1 kGy after a storage period of up to 30 months after the irradiation. In summary, our study tends to confirm that the IR-RF signal is stable and does not suffer from athermal fading. The observed saturation dose is in accordance with values published in the literature. It renders IR-RF a potent chronological tool; however, it appears that equivalent dose values above 1.2 kGy should be considered cautiously. Our study is limited to a single sample, and future studies may confirm and further constrain our results. Measurement and processed data of our study are available open access.